2015
DOI: 10.1007/s00122-015-2569-y
|View full text |Cite
|
Sign up to set email alerts
|

Loci, genes, and mechanisms associated with tolerance to ferrous iron toxicity in rice (Oryza sativa L.)

Abstract: A genome-wide association study in rice yielded loci and candidate genes associated with tolerance to iron toxicity, and revealed biochemical mechanisms associated with tolerance in contrasting haplotypes. Iron toxicity is a major nutrient disorder affecting rice. Therefore, understanding the genetic and physiological mechanisms associated with iron toxicity tolerance is crucial in adaptive breeding and biofortification. We conducted a genome-wide association study (GWAS) by exposing a population of 329 access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 52 publications
6
72
0
Order By: Relevance
“…Association mapping for each trait included the determination of SNPs exceeding a significance value of −log 10 P >4.0 (an arbitrary threshold that had been previously applied by others, e.g. Ueda et al , 2015; Wissuwa et al , 2015), analyses of LD blocks surrounding each highly significant (−log 10 P >4.0) SNP, and curation of a list of candidate genes contained within these blocks (Supplementary Table S3). Out of 26 863 markers included in this analysis, we identified 18 SNP markers that satisfied the established threshold (Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Association mapping for each trait included the determination of SNPs exceeding a significance value of −log 10 P >4.0 (an arbitrary threshold that had been previously applied by others, e.g. Ueda et al , 2015; Wissuwa et al , 2015), analyses of LD blocks surrounding each highly significant (−log 10 P >4.0) SNP, and curation of a list of candidate genes contained within these blocks (Supplementary Table S3). Out of 26 863 markers included in this analysis, we identified 18 SNP markers that satisfied the established threshold (Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Manhattan plots were displayed, and the threshold for significantly associated markers was set to P <0.0001 (i.e. –log 10 P >4.0), as previously suggested (Zhao et al , 2011; Matthus et al , 2015; Ueda et al , 2015). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuation of protein level under higher Fe concentration is possibly due to the induction of stress proteins, which may comprise various antioxidant enzymes and metabolites (Lamhamdi et al, 2010). Baruah et al (2001) also reported that rice plants tolerant to higher Fe showed consistent total soluble protein in shoots. EL, a common damage in plasma membrane due to metal toxicity, was significantly changed in BR 27 plants under excess Fe.…”
Section: Discussionmentioning
confidence: 84%
“…They consisted of 20 wild species of the Oryza genus with different countries of origin, one cross of O. glaberrima and O. barthii and two O. sativa varieties, for which crosses with wild relatives have been made (IRRI 154 and Curinga). In addition, 15 accessions of cultivated rice species (O. sativa and one O. glaberrima) that had previously been screened in Fe toxicity experiments [26,32,33] were added from the seed stocks of the Institute of Crop Science and Resource Conservation (INRES).…”
Section: Plant Materialsmentioning
confidence: 99%